Cheju and Kwangju: Healing the National Trauma in the Works of Han Kang - Justyna Najbar-Miller (Politeja)
The paper will focus on two novels written by a well-known South Korean writer, Han Kang (1970-), namely Here Comes the Boy (Sonyŏn i onda, 2014) and I Do Not Bid Farewell (Chakpyŏl haji annŭnda, 2021), which deal respectively with the events of the Kwangju Uprising in 1980 and the Cheju Uprising in 1948, exposing the massacres of civilians by South Korean authorities. The aim of the article is to present these tragic events, which were not accurately portrayed in the Republic of Korea until the end of 1980s and – using Donald Kalsched’s theory of trauma – demonstrate that Han Kang acts like a shaman crossing the boundaries between an ordinary and non-ordinary reality in order to work through the national trauma, heal the broken souls and bring peace to the traumatized communities.